Plasticity in Sexual Dimorphism Enhances Adaptation of Dioecious Vallisneria natans Plants to Water Depth Change - Zhou, Yin; Li, Lei; Song, Zhiping (Frontiers in Plant Science, 2019)
Sexual dimorphism in vegetative and reproductive traits is associated with contrasting strategies of males and females for response to varied environmental conditions, causing sex-specific reproduction success and consequently long-distance dispersal and colonization. Aquatic plants usually exhibit rich phenotypic plasticity and great diversity in reproductive systems, but the influence of aquatic conditions on the plasticity of sexual dimorphism has received less attention. Using a common garden experiment with dioecious submerged plant Vallisneria natans grown at various water depths simulating different light availability, we measured variations in 20 traits for females and 19 traits for males (total = 540 plants from 30 seed families) including morphology, reproductive traits and photosynthesis. We investigated sex-specific plastic responses and variation of sexual dimorphism in response to water depth change. Females displayed much greater leaf length, vegetative biomass and resource allocation to reproduction than males at all depths, whereas spathe number and gamete production per spathe displayed reverse pattern. Besides most traits in each sex (16 in female and 12 in male) showing striking phenotypic plasticity, the degree of sexual dimorphism increased significantly for total biomass and reproductive investment, but decreased for leaf length, spathe number and flowering ramet percentage in low light and deep water. Females varied more than males in leaf length, total biomass, reproductive investment, length and biomass of reproductive organs and rate of photosynthesis in response to decreased underwater light availability, suggesting that female has greater plasticity than male. These findings illustrated considerable plasticity in the degree of sexual dimorphism in a variety of vegetative and reproductive traits across different environments driven by the contrasting reproductive functions of the sexes in relation to pollen and seed dispersal. Females of V. natans responded more plastically than males to low light conditions resulted from water depth variation in either aboveground vegetative growth or reproduction. This study provides novel insight into adaptive strategies of submerged dioecious macrophytes to survive and increase fitness in freshwater habitats.